Desempenho financeiro dos projetos de empreendimentos imobiliários e sau influênica nos preços das ações de empresas com real state - Barzi, Luciana Andrade [UNIFESP] (2015)
The purpose of this research is to analyze the relationship regarding the financial results of the residential real estate as to the three largest developers based in the city of São Paulo, and as well evaluate oscilations in the price of its shares within the Stock Exchange Market, to conclude whether or not there is evidence of influence between these variables. The text contextualizes the theories and practices of the real estate industry in Brazil. A brief history of the evolution in Brazilian real estate market is presented, especially after the entry of companies in the capital market. The three chosen companies have great participation in the national real estate market. Share prices were obtained from Economática site. Besides the historical stock price, the analysis also left the cash flows of the projects executed by these companies, defined in the period between 2008 and 2014. The return of stock prices is calculated, the monthly cash flows and calculate the abnormal return. In addition, linear regression model is used, individually (per project) and in the group of enterprises by company. At the end there is a presentation of a review of the results pertaining each company and the final considerations about the relationship between the financial results of real estate projects and the Companies' market value. The results obtained in this study indicated no evidence of cash flows correlation of the projects and the evolution of stock prices, suggesting that the analysis using only cash flow does not provide the final and definitive share value of a real estate company.